Examining the Role of the School Environment to Enhance Indonesian Middle School Students’ Numeracy - Ermita, Ermita; Samosir, Rosauli Novalina; Miftahul Jannah; Nita Anggriani; Aisyiah Restutiningsih Putri Utami; Muhammad Isbar Pratama (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2025)
This study investigates how the school environment, both physical and non-physical, can support the development of middle school students’ numeracy in Indonesia. Conducted during the Kampus Mengajar program, the study used a mixed methods approach in two junior high schools in North Sulawesi. Environmental interventions included numeracy-themed visual displays, games, and integration of numeracy across subjects and projects. A total of 48 Grade 8 students were involved in pre- and post-tests, supported by interviews and observations. Results showed statistically significant improvements in students’ numeracy scores after the intervention. Qualitative data revealed that students engagement in classroom increased. Moreover, the interventions received positive perceptions from students, teachers, and principals. Both schools faced some challenges, such as space limitations and teachers engagement was mostly limited to those teaching science and mathematics. The findings suggest that designing a school environment, both physical and non-physical, that is numeracy-rich can enhance students' numeracy skills, even with limited resources. Further studies are recommended to explore long-term impacts and broader implementation.